Burden of osteoarthritis in Indonesia: A Global Burden of Disease (GBD) study 2019 - Butarbutar, John CP.; Basuki, Pamela; Sungono, Veli; Riantho, Albert; Fidiasrianto, Kevin (Narra Sains Indonesia, 2024)
Osteoarthritis (OA) is a complex and common condition, especially affecting the knees due to their weight-bearing role. Traditionally seen as a degenerative disease, OA is now understood to have both mechanical and inflammatory causes. Despite its increasing prevalence, there is limited data on OA in Indonesia, resulting in low awareness among clinicians and the public. The aim of this study was to describe the OA burden in Indonesia, focusing on its prevalence, incidence, and years lived with disability (YLD) from 1990 to 2019, using data from the Global Burden of Disease (GBD) study 2019. A descriptive cross-sectional study was conducted to examine the prevalence, incidence, and YLD of OA in Indonesia from the GBD study 2019. OA prevalence and YLD were compared to other countries according to similar social demographics and geographical proximity. OA YLD was also compared to the top causes of death and disability YLD in Indonesia. The study found that OA cases in Indonesia more than doubled from 1990 to 2019, with increases of 153.12% in males and 143.36% in females. Similar trends were observed for knee OA. The age-standardized prevalence rate in Indonesia increased by 10.03% in males and 8.42% in females, and these were higher compared to China, India, Singapore, and the global average. Younger people had a higher OA prevalence rate growth than older groups. The incidence rate for OA also rose significantly, with males seeing a 10.89% increase to 290 per 100,000 people and females with an 8.57% increase to 384 per 100,000 people. Despite lower overall burden rates compared to some countries, Indonesia experienced significant growth in YLD due to OA (12.16% in males and 9.65% in females) since 1990. Although OA was less burdensome than stroke, diabetes, low back pain, and chronic obstructive pulmonary disease (COPD), its YLD growth rate was higher. In conclusion, OA prevalence and incidence in Indonesia significantly increased from 1990 to 2019, with a notable rise among younger populations. OA had a higher YLD growth compared to several other major diseases in Indonesia, highlighting the need for early detection and preventive measures, particularly for the younger population.